Early elementary mathematics lessons to explore, understand, and respond to social injustice - Koestler, Courtney; Ward, Jennifer, 1963-; Zavala, Maria del Rosario; Bartell, Tonya Gau (Thousand Oaks : Corwin, 2023)
Written for teachers committed to developing equitable and just practices through the lens of mathematics content and practice standards as well as social justice standards, this book will help connect early elementary mathematics content to children's daily lives, fortify their understanding, and expose them to issues that will support them in becoming active citizens and leaders.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Mathematics -- Study and teaching (Elementary)